Bioactivity of extracts of Alstonia boonei (Apocynaceae) De wild stem bark against Maruca vitrata (Lepidoptera: Pyralidae) Fabricius - Oigiangbe, O.N.; Igbinosa, I.B.; Tamo, Manuele (2007)
The bioactivity of water and methanol extracts of Alstonia booneii stem bark against Maruca vitrata Fabricius, was studied in the laboratory through a bioassay. When incorporated into the artificial diet at 0.0% (control), 1.0%, 2.5 %, 5.0 %, and 10.0 % concentrations, respectively, both extracts significantly reduced survival, growth and development of M. vitrata larvae. The survival was 95.83 %. 70.83%. 62.50% and 4.17 % on treatments containing the water extract and 91.67 %, 83.33 %, 53.33 % 12.50% on that containing the methanol extract at the above concentrations respective, compared to the control which was 100.00 %. At 10 days after infestation (DAI), the LC for the water extract was 4.48% while that of the methanol extract was 4.98 %. The larvae reared on the treatment containing the water extract gain more weight (56.13 mg. 59.24 mg. 29.93 mg) than those reared on the treatments containing the methanol extract (31.82 mg. 14.10 mg, 1.93 mg) at 1.0%,2.5 %, and 5 % concentrations, respectively. Almost all the larvae reared on the diets containing the water extract of A. boonei which survived up to 20 DAI were able to pupate but 9.0%, 30.0 % and 100.0 % of those reared on the diet containing 1.0 %, 2.5 % and 5.0 % of the methanol extract, respectively, could not. We conclude that the water extract of the stem bark of A. boonei contains some toxic substances while the methanol extract has some antifeedant or repellent substances.